Targeted Immunotherapy in Urological Malignancies - Abubakar Sadiq Muhammad (Highlights on Medicine and Medical Research Vol. 13, 2021)
Targeted immunotherapy has revolutionized the treatment of urological malignancies. The approach tries to recapitulate the natural ability of the immune system to destroy cancer cells. This can be by use of non-specific agents such as recombinant Bacillus Calmette-Guerin (BCG) or use of specific agents such as immune checkpoint inhibitors (ICI) and anti-tumor vaccine. There was tremendous success in the use of BCG to reduce tumour recurrence and progression in non-muscle invasive bladder cancer (NMIBC). Of recent, immune checkpoint inhibitors are used to downstage muscle invasive (MIBC) to NMIBC or even achieved cure at the level of clinical trials. The ICI has shown a positive response in advanced renal cell carcinoma (RCC), castration-resistant prostate cancer (CRPC), refractory germ cell tumour of the testis. The ICI such as pembrolizumab, atezolizumab and ipilimumab achieved better response than sunitinib, a tyrosine kinase inhibitor; which is the standard of care in advanced RCC. Sipuleucel-T, an autologous prostatic acid phosphatase dendritic cell loaded vaccine, has been approved by US Federal Drug Administration Agency for CRPC. Immunotherapy is associated with manageable toxicity such as infusion reactions and immune-related adverse event which respond to the use of corticosteroids with or without cessation of the therapy.